Construction and validation of BRAF mutation diagnostic model based on ultrasound examination and clinical features of patients with thyroid nodules - Xu, Chan; Fang, Jianqiang; Li, Wanying; Sun, Chenyu; Li, Yaru; Lowe, Scott; Bentley, Rachel; Chen, Shuya; He, Cunyu; Li, Xinxin; Wang, Bing; Yin, Chengliang; et al. (Frontiers in Genetics, 2022)
Introduction: Fine Needle Aspiration (FNA) is currently the most popular method for identifying benign and malignant thyroid nodules, although sometimes its diagnostic sensitivity is limited, necessitating the use of genetic testing and other modalities as a secondary diagnosis. Thyroid nodule diagnostic accuracy can be improved by combining mutations in the B-Raf proto-oncogene serine/threonine kinase (BRAF) with FNA. We aimed to create a nomogram diagnostic model based on the clinical and ultrasound characteristics of patients with BRAF mutations to aid in the identification of benign and malignant thyroid nodules using FNA in this study. Methods: From April 2018 to December 2021, 275 patients with thyroid nodules who underwent ultrasonography and BRAF gene testing (137 positive and 138 negative) were included from Xianyang Central Hospital. The clinical and ultrasound characteristics of the patients were used to develop a nomogram diagnostic model of BRAF gene mutation and to validate and evaluate the usefulness of the model. Results: Independent risk factors for BRAF mutations included: focal strong echogenicity (microcalcifications, OR=3.04, 95%CI=1.41-6.58, p=0.005), hypoechogenicity (OR=3.8, 95%CI=1.14-12.61, p=0.029), lymph node metastases (OR=3.54, 95%CI=1.43-8.75, p = 0.006), margin (lobulated, OR=3.7, 95%CI=1.66-8.23, p=0.001; extrathyroidal invasion, OR=2.81, 95%CI=1.11-7.06, p=0.029) and shape (vertical position, OR=2.7, 95%CI=1.11-6.59, p=0.029). The area under the curve (AUC) of the receiver operating characteristic (ROC) curve for the BRAF mutation diagnostic model constructed on these factors was 0.806 (95% CI=0.754-0.851), and using 39.5% as the threshold probability of making a clinical decision. The results of the validation and clinical utility evaluation showed that our model had good predictive performance and clinical application value. Conclusion: Our nomogram diagnostic model based on clinical and ultrasound features of patients accurately predicted the outcome of BRAF gene mutations.